Enhancing students’ critical thinking through literary analysis: a systematic review - Kinanti Resmi Hayati; Much Koiri (Tell : Teaching of English Language and Literature Journal, 2026)
This paper reviews empirical studies on the relationship between literary understanding and critical thinking skills among students. Those studies considered are published between 2013 and 2025, totaling fifteen articles. In this systematic review, we examine empirical studies that treat the specific view, analysis, and interpretation of texts as an activity and examine how this text-based activity affects critical thinking skills. As a comprehensive approach to the use of literary texts in developing critical-thinking skills, this inquiry responds to extant studies. Results are centred on the advantages and difficulties of implementing literary comprehension strategies to develop critical literacies for both researchers and practitioners.